2015
DOI: 10.1097/tp.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Related Breathing Disorders and Lung Transplantation

Abstract: We have observed a significant prevalence of obstructive sleep apnea syndrome in patients in waiting list for LT, and LT has an important influence in the evolution of the disorder. In our series, LT has somehow affected the stability of upper airway and ventilatory mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…High prevalence at 12 months post‐LTX was also shown in a study that evaluated 20 patients before, at 6 and 12 months post‐LTX. This study showed that SDB prevalence was high at 6 months post‐LTX and remained high at 12 months post‐LTX 12 …”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…High prevalence at 12 months post‐LTX was also shown in a study that evaluated 20 patients before, at 6 and 12 months post‐LTX. This study showed that SDB prevalence was high at 6 months post‐LTX and remained high at 12 months post‐LTX 12 …”
Section: Discussionmentioning
confidence: 61%
“…Yet, there is a high variability in reported prevalence. Prevalence of SDB after LTX was not significantly increased at 1 month after LTX but was increased at 6 months and 1 year after LTX 12,13 …”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations